Improving livestock productivity: Assessment of feed resources and livestock management practices in Sudan-Savanna zones of West Africa - Ayantunde, Augustine A.; Amole, Tunde A. (Academic Journals, 2016)
Evaluation of existing and potential feed resources was conducted in Orodora district in the Southern region of Burkina Faso using Feed Assessment Tool (FEAST). The assessment was carried out through focus group discussions and individual interviews in Mahon and Sayaga communities in Orodara district. The study sites were characterized by mixed crop-livestock production systems. Seventy-percent of cropping activities were focused on fruit tree cultivation while food crop production accounted for the rest. Livestock species (predominantly local breeds) in the area included cattle sheep, goat, pig, poultry and donkey which are kept for different purposes. The main source of household income is crop production while livestock production contributed 35 and 45% to the household income in Mahon and Sayaga, respectively. In both study sites, natural grazing contributes highest (49 and 64% respectively) to the dry matter (DM) content of the total diet. Cultivated fodder contributed 1% of dry matter (DM), metabolizable energy and crude protein to the total diet of the existing feed resource in Mahon, while farmers in Sayaga depended more on purchased feed than in Mahon. Constraints to livestock production in the study sites included shortage of water in the dry season, insufficient quantity and quality of feed in the late dry season of the year and high cost of veterinary drugs and services. To mitigate these constraints farmers suggested an integrated approach to improve livestock production through: construction of small reservoir to provide water for human and animal consumption; training on the integration of forage legume into both tree and arable cropping, and efficient utilization of available feed resources; establishment of a veterinary service and drug centre in the village; better management of the existing water resources.